How much work experience do you need to get your first job? The macroeconomic implications of bias against labor market entrants - Shisham Adhikari; Athanasios Geromichalos; Ioannis Kospentaris (University of California, Department of Economics, 2023)
The first step in a worker's career is often particularly hard. Many firms seeking workers require experience in a related field, so a vicious circle is created, whereby an entry level job is required in order to get an entry level job. Consequently, entrant workers have lower job-finding rates and longer unemployment durations than the unemployed who have looked for a job in the past. To study the welfare implications of these observations, we consider a version of the DMP model where firms who match with entrant workers have to incur training costs. As a result, firms are biased against entrant workers, who, in turn, stay unemployed for a prolonged period of time, exposing themselves to a persistent skill loss shock. In this environment, an obvious market failure arises. Firms who hire entrant workers provide a benefit to society by helping these workers stay unemployed for a shorter period of time, thus reducing the probability of skill loss. But since firms cannot internalize this societal contribution, they choose to discriminate against entrant workers causing a welfare loss. We use a calibrated version of the model to quantitatively assess the effectiveness of three government interventions, whose common goal is to reduce bias against entrant workers. We find that the most effective intervention takes the form of an "internship", where firms can hire entrant workers at an (exogenous) lower wage.
Keywords: E24; E60; J24; J64; 330; search and matching; unemployment; labor market entrants; training; skills